PEDIATRIC FEVER. USE OF NON-STEROID ANTI-INFLAMMATORY DRUGS (NSAID’S) - М.D. Bakradze; D.Yu. Akoeva (Вопросы современной педиатрии, 2011)
Fever is the commonest symptom of pediatric diseases. During first two years of life the child usually experiences about 4–6 fever episodes that are normally cause of enormous parental concern. That is why fever is one of the commonest reasons of calling a pediatrician, and it’s quite natural that physicians tend to prescribe anti-fever medications. Due to mass consumption of various febrifuges it’s quite important to choose the safest of them, as well as informing doctors and parents about certain cases when febrifugal treatment is necessary. Key words: children, fever, febrifuges, non-steroid anti-inflammatory drugs. (Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (5): 133–137.)